Integrated approach for the management of Sclerotinia sclerotiorum (Lib.) de Bary, causing stem rot of chickpea - PANDEY, PANKAJ; KUMAR, RAVINDER; MISHRA, PRASHANT (Indian Phytopathology, 2011)
Matco, carbendazim, thiophenate methyl, propiconazole and hexaconozle were found to be most effective fungicide and Trichoderma virens was found strongly antagonistic causing 69.08% inhibition of mycelial growth of S. sclerotiorum in vitro. The seed treatment with garlic extract 10% (1% w/v) was the most effective in reducing the disease incidence (92.22 per cent) and increased germination (12.36 per cent) followed by neem powder @ 6 g/kg seed which resulted in the reduction of disease incidence (86.83 per cent) and increased germination similar as garlic extract, respectively. In the field experiments, vermi-compost @ 5.0 tones/ha + T. harzianum @ 5.0 kg/ha was the most effective in reducing the disease incidence (72.73 per cent) and increase in grain yield (39.69 per cent) followed by FYM @ 2.5 tones/ha + T. harzianum @ 5.0 kg/ha, which resulted in the reduction of disease incidence (64.85 per cent) and increasing the grain yield up to 38.17 per cent. Minimum reduction in disease incidence was found in foliar spray with P. fluorescens @ 5.0 g/liter (14.55 per cent) and minimum increase in grain yield (15.27 per cent) was also observed.